Thermoelectric material having network heterostructure providing
By mixing and sintering nanoparticles of components A and B in bulk synthesis to form a network heterostructure, the problem of low efficiency in existing thermoelectric materials is solved, and the preparation of highly efficient thermoelectric heterostructure materials is realized, which improves Seebeck coefficient and electrical conductivity and reduces thermal conductivity.
Patent Information
- Application Number
- CN202380095915.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-14
- Filing Date
- 2023-11-24
- Publication Date
- 2025-11-18
AI Technical Summary
Existing thermoelectric materials have low thermoelectric efficiency, and traditional methods for preparing nanostructures are complex and expensive, making it difficult to achieve efficient nanoscale honeycomb network thermoelectric heterostructures in bulk synthesis.
By mixing nanomaterial powder of component A with powder of component B in a specific ratio range, heating and shaking under vacuum, then rapidly cooling and grinding into powder, filling into a mold, and finally sintering in a vacuum chamber, a network heterostructure nanomaterial is formed.
A thermoelectric figure of merit of 2.1 and 2.6 were achieved for p-type and n-type thermoelectric heterostructures near room temperature, respectively, which improved the Seebeck coefficient and electrical conductivity, reduced the thermal conductivity, and simplified the preparation process.
Smart Images

Figure CN120982236A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to thermoelectric materials, and more specifically, to methods for developing and improving the efficiency of thermoelectric materials. Background Technology
[0002] Bulk pure metals are not considered suitable candidates for thermoelectric applications because the differences in their chemical potentials are negligible. Initially, intermetallic materials such as nickel-chromium, nickel-aluminum, platinum-rhodium, and constantan were used as thermoelectric materials, particularly for temperature measurement thermocouples. However, their application combinations remain limited due to their poor thermoelectric efficiency.
[0003] With technological advancements, it has been discovered that highly doped semiconductors possess the ability to generate both n-type and p-type thermoelectric phenomena. This is due to the shift in the Fermi level (the chemical potential in a metal) caused by the change in doping type. Semiconductor thermoelectric materials are far more efficient than intermetallic alloys because the bandgap value controls the operating temperature, the relative positions of the Fermi levels between p-type and n-type materials form a thermocouple rather than coupling with a Seebeck coefficient reference copper, and the lattice thermal conductivity is reduced.
[0004] Most research and development efforts have ultimately shifted to semiconductors as potential thermoelectric materials. Due to favorable compositional control parameters, bismuth-antimony chalcogenides have been identified as suitable thermoelectric materials for applications above room temperature.
[0005] The thermoelectric efficiency parameter of any material is established as the thermoelectric figure of merit (ZT), which is defined as ZT = (S 2 Z is given by σ / κ)T, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature. Therefore, Z is determined by the ratio of the power factor (PF) to κ, where the power factor is defined as PF = S. 2 The value of σ. ZT remained near one for decades until theoretical predictions in the prior art regarding the improvement of ZT through quantum confinement {LDHicks and MSDresselhause, “Thermoelectric figure of merit of a one-dimensional conductor,” Physical Review B, Vol. 47, p. 16631 (1993); and “Effect of quantum-well structures on thermoelectric figure of merit,” Physical Review B, Vol. 47, p. 12727 (1993)} spurred a renewed interest in research and development.
[0006] Experimental reports on ZT enhancement through quantum confinement are limited to quantum wells {LDHicks et al., “Experimental study of the effect of quantum-well structure on thermoelectric figure of merit”, Physical Review B, Vol. 53, p. R10493 (1996); US Patent No. 7,400,050B2}, and quantum wires {J. Heremans and C.M. Thrush, “Thermoelectric power of bismuth nanowires”, Physical Review, Vol. 59, p. 12579 (1999); Yu-Ming Lin et al., “Transport properties of Binanowire array”, Applied Physics Letters, Vol. 76, p. 3944 (2000); “Semimetal-semiconductor transition in Bi 1-x Sb xAlloy nanowires and their thermoelectric properties, Applied Physics Letters, Vol. 81, p. 2403 (2002); Patent Publication No. US2014 / 0024202 A1} and superlattices {TC Harman et al., “Quantum dot superlattice thermoelectric materials and devices,” Science, Vol. 297, p. 2229 (2002); Hiromichi Ohta et al., “Giant thermoelectric Seebeck coefficient of a two-dimensional electron gas in SrTiO3,” Natural Materials, Vol. 6, p. 129 (2007); JCCaylor et al., “Developing PbTe-based superlattice structures with enhanced thermoelectric performance,” IEEE ICT, p. 492 (2005); S. Ghamaty et al., “Quantum well thermoelectric devices and applications,” IEEE ICT, p. 563 (2003); Patent Publication No. US2011 / 0062420 A1; Patent Publication No. US2007 / 0084499 A1; US Patent No. 5,550,387 dated August 27, 1996; US Patent No. 5,436,467 dated July 25, 1995; US Patent No. 9,136,456B2; US Patent No. 7,400,050B2; US Patent No. 8,569,710B2; PCT International Patent Publication No. WO 03 / 096438A2; PCT International Patent Publication No. WO 01 / 17035 A1; PCT International Patent Publication No. WO98 / 42033; PCT International Patent Publication No. WO 98 / 42034}. These structures require complex and expensive technologies for development, such as molecular beam epitaxy (MBE). Purpose of the invention
[0007] The purpose of this disclosure is to provide an easily scalable method for obtaining thermoelectric heterostructure materials with nanoscale honeycomb mesh morphology in bulk synthesis.
[0008] Another objective of this disclosure is to realize both p-type and n-type thermoelectric heterostructure materials through the same process.
[0009] Another objective of this disclosure is to obtain thermoelectric heterostructure materials with improved thermoelectric efficiency.
[0010] Another object of this disclosure is to provide thermoelectric heterostructure materials with improved Seebeck coefficient, increased electrical conductivity, reduced thermal conductivity and improved thermoelectric figure of merit. Summary of the Invention
[0011] According to an embodiment, a method for obtaining a network heterostructured nanomaterial by synthesis is disclosed. The method includes mixing a nanomaterial powder of component A with a powder of component B in a ratio selected from a range of 95:05 to 75:25 to obtain a mixture thereof. The method further includes heating the obtained mixture under vacuum to melt component B in the mixture while shaking the mixture during heating. The method also includes quenching the heated mixture in air to obtain a quenched mixture. The method further includes grinding the quenched mixture containing components A and B into a powder form. The method also includes filling the powder form of the quenched mixture into a pre-designed mold. The method further includes consolidating the powder form of the quenched mixture by sintering in a vacuum chamber to obtain a network heterostructured nanomaterial.
[0012] According to an embodiment, a heterostructure thermoelectric nanomaterial is disclosed. The heterostructure thermoelectric nanomaterial includes materials of formula Bi. x Sb 2-x D y M 3-y / D δ The heterostructure, in which Bi x Sb 2-x D y M 3-y Let A be component A and D be component B, wherein elements D and M are selected from the group including Te, Se, and S; wherein the values of x, y, and δ are in the range of 0 to 3.
[0013] In the embodiments, the nanostructure of the heterostructure thermoelectric nanomaterial forms a network heterostructure morphology at the nanoscale in the range of 1 nm to 10 nm, wherein component B has a honeycomb network structure with gaps between the honeycomb network structures, and wherein the gaps are filled with component A.
[0014] In an embodiment, the thermoelectric efficiency of the network heterostructure is improved by: quantum confinement in the metal or semiconductor layer of component B, band shift of the quantum confinement obtained through the barrier layer of the semiconductor thermoelectric nanomaterial of component A, and carrier injection from the barrier layer of component A to the quantum well layer of component B to obtain thermoelectric heterostructures with different polarities.
[0015] In the embodiment, p-type tellurium / Sb 2-x Bi x The maximum thermoelectric figure of merit (ZT) for the Te3 heterostructure near room temperature is 2.1.
[0016] In the embodiment, n-type tellurium / Bi2Te 3-x Se x The maximum thermoelectric figure of merit (ZT) for the heterostructure near room temperature is 2.6. Attached Figure Description
[0017] To gain a more complete understanding of exemplary embodiments of the present technology, reference is now made to the following description taken in conjunction with the accompanying drawings, wherein:
[0018] Figure 1 A flowchart illustrating the method provided by an exemplary embodiment of this disclosure is shown.
[0019] Figure 2 It is a photograph of heterogeneous solidified particles.
[0020] Figure 3 The image shown is a high-resolution transmission electron microscopy (HR-TEM) image of a heterostructure sample provided in an embodiment of the present disclosure at the 100 nm scale, which shows the honeycomb network of component B and the voids filled with component A.
[0021] Figure 4 The image shown is an HR-TEM image of a heterostructure sample provided in an embodiment of the present disclosure at a scale of 50 nm, which shows the honeycomb network of component B and the voids filled with component A.
[0022] Figure 5 The image shown is an HR-TEM image of a heterostructure sample provided in an embodiment of the present disclosure at a 5 nm scale, which shows a small number of quintuplets and a small number of atomic layers of component B.
[0023] Figure 6An HR-TEM image of a heterostructure sample provided in an embodiment of the present disclosure is shown at a 5 nm scale, with a small number of quintuplets and a small number of atomic layers of component B shown at another location in the image.
[0024] Figure 7 The embodiments of this disclosure provide different δ values for Te. δ / Bi x Sb 2-x A graphical representation of the Seebeck coefficient (S) of the Te3 heterostructure as a function of temperature.
[0025] Figure 8 The embodiments of this disclosure provide different δ values for Te. δ / Bi x Sb 2-x A graphical representation of the measured conductivity (σ) of the Te3 heterostructure as a function of temperature.
[0026] Figure 9 The embodiments of this disclosure provide different δ values for Te. δ / Bi x Sb 2-x The power factor (S) of the Te3 heterostructure is calculated based on the measured values of S and σ. 2 A graphical representation of the σ value as a function of temperature.
[0027] Figure 10 The embodiments of this disclosure provide different δ values for Te. δ / Bi x Sb 2-x The measured thermal diffusivity of the Te3 heterostructure as a function of temperature is represented graphically.
[0028] Figure 11 The embodiments of this disclosure provide different δ values for Te. δ / Bi x Sb 2-x The thermal conductivity of the Te3 heterostructure, calculated from measured thermal diffusivity, specific heat, and solid density values, is represented graphically as a function of temperature.
[0029] Figure 12 The embodiments of this disclosure provide different δ values for Te. δ / Bi x Sb 2-x The thermoelectric figure of merit of the Te3 heterostructure, calculated based on the power factor and thermal conductivity, is represented graphically as a function of temperature.
[0030] Figure 13 The p-type Te provided by the embodiments of this disclosure is shown. δ / Bix Sb 2-x Graphical representation of temperature-dependent (a) Hall mobility and (b) carrier concentration of the optimal performance composition of the Te3 heterostructure.
[0031] Figures 14(a) and (b) illustrate the Te provided by embodiments of this disclosure. δ / Bi x Sb 2-x Graphical representation of the Hall resistance and longitudinal resistance of the Te3 heterostructure as a function of the applied magnetic field at room temperature.
[0032] Figure 15 The embodiments of this disclosure provide different δ values for Te. δ / Bi2Te 3-y Se y A graphical representation of the Seebeck coefficient (S) of a heterostructure as a function of temperature.
[0033] Figure 16 The embodiments of this disclosure provide different δ values for Te. δ / Bi2Te 3-y Se y A graphical representation of the measured electrical conductivity (σ) of a heterostructure as a function of temperature.
[0034] Figure 17 The embodiments of this disclosure provide different δ values for Te. δ / Bi2Te 3-y Se y The power factor (S) of the heterostructure is calculated based on the measured values of S and σ. 2 A graphical representation of the σ value as a function of temperature.
[0035] Figure 18 The embodiments of this disclosure provide different δ values for Te. δ / Bi2Te 3-y Se y The measured thermal diffusivity of a heterostructure as a function of temperature is represented graphically.
[0036] Figure 19 The embodiments of this disclosure provide different δ values for Te. δ / Bi2Te 3-y Se y A graphical representation of the thermal conductivity of a heterostructure as a function of temperature, calculated from measured thermal diffusivity, specific heat, and solid density values.
[0037] Figure 20 The embodiments of this disclosure provide different δ values for Te. δ / Bi2Te3-y Se y The thermoelectric figure of merit of a heterostructure, calculated based on the power factor and thermal conductivity, is represented graphically as a function of temperature.
[0038] Figure 21 The n-type Te provided by the embodiments of this disclosure is shown. δ / Bi2Te 3-y Se y Graphical representation of temperature-dependent (a) Hall mobility and (b) carrier concentration of the optimal performance composition of the heterostructure.
[0039] Figures 22(a) and (b) illustrate the Te provided by embodiments of this disclosure. δ / Bi2Te 3-y Se y Graphical representation of the Hall resistance and longitudinal resistance of the heterostructure as a function of the applied magnetic field at room temperature. Detailed Implementation
[0040] In the following description, numerous specific details are set forth for purposes of explanation in order to provide a thorough understanding of this disclosure. However, it will be apparent to those skilled in the art that this disclosure may be practiced without these specific details.
[0041] In this specification, references to "an embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment of this disclosure. The appearance of the phrase "in an embodiment" throughout the specification does not necessarily refer to the same embodiment, nor is it intended to be a separate or alternative embodiment that is mutually exclusive with other embodiments. Furthermore, various features that may be exhibited by some embodiments but not by others are described. Similarly, various requirements are described that may be requirements of some embodiments but not by others.
[0042] Furthermore, although the following description contains numerous details for illustrative purposes, those skilled in the art will understand that many variations and / or alterations to these details are possible within the scope of this disclosure. Similarly, although many features of this disclosure are described relative to each other or in combination with each other, those skilled in the art will understand that many of these features may be provided independently of the others. Therefore, the formulation of this specification does not diminish the generality of this disclosure and does not impose any limitations on it.
[0043] This disclosure relates to heterostructured thermoelectric nanomaterials and a method for obtaining network-structured heterostructured nanomaterials with metal-semiconductor heterostructures. The method is also applicable to semiconductor-semiconductor, metal-insulator, and semiconductor-insulator heterostructures. The use of such heterostructures, with a nanoscale quantum well layer network resembling a honeycomb structure and filled with a barrier layer material, requires quantum confinement and electrical transport. This method for preparing thermoelectric heterostructures is easily scalable. Applications of this novel form are typically in electronic devices, and particularly in thermoelectric devices.
[0044] Figure 1 A flowchart of a method 100 for obtaining a network heterostructured nanomaterial from component A and component B is shown.
[0045] In step 102, the powder of nanomaterial component A is mixed with the powder of component B. Component A and component B can be selected from the group consisting of metals, semiconductors, and insulators. In an embodiment, component A can be a metal, a semiconductor, or an insulator, and component B can be a metal or a semiconductor. Furthermore, component A can be selected from highly doped semiconductor thermoelectric nanomaterials. In an embodiment, component A is selected from materials with a carrier concentration range of 10-1. 19 / cm 3 Up to 10 21 / cm 3 The nanomaterials are p-type or n-type highly doped semiconductor nanomaterials. In the foregoing embodiments, the selection of components A and B is made in such a way that the melting point of component A is greater than that of component B. Furthermore, components A and B can be selected such that component B has a lower chemical potential relative to the corresponding component A. In the embodiments, after components A and B have been selected, they can be mixed in a ratio that can vary between 95:05 and 75:25 to obtain a mixture.
[0046] Regarding step 102 above, in this embodiment, component B is selected from the group consisting of tellurium, bismuth, and zinc, and component A is selected as Bi2Te. 3-x Se x , where x is in the range of 0.1 to 1.
[0047] In another exemplary embodiment, component B is selected from the group consisting of tellurium, bismuth, and zinc, and component A is selected as Sb. 2-x Bi x Te3, where x is in the range of 0.1 to 1.
[0048] In another exemplary embodiment, component B is selected from the group consisting of Bi2Te3 and Sb2Te3, and component A is selected from the group consisting of Bi2Se3, Bi2S3, Sb2Se3 and Sb2S3.
[0049] In step 104, the mixture obtained by mixing components A and B is heated under vacuum to the melting point of component B. The mixture is agitated during heating. In this embodiment, the mixture is heated at a temperature that keeps component A solid and only component B melts. The agitation of component A and liquefied component B is carried out in a quartz ampoule for 1 to 5 hours. Thus, in step 104, agitation of one solid component and one liquid component occurs.
[0050] At step 106, the heated mixture is quenched in air to obtain a quenched mixture. In an embodiment, the quenched mixture is collected by breaking a quartz ampoule.
[0051] At step 108, the quenched mixture of components A and B is milled to obtain a quenched mixture in powder form. In this embodiment, the quenched mixture is powdered using conventional milling techniques.
[0052] In step 110, the quenched mixture in powder form is filled into a pre-designed mold. In an embodiment, the graphite mold has an inner diameter in the range of 10 mm to 40 mm.
[0053] At step 112, a network-like heterostructured nanomaterial is obtained by sintering the mixture in a vacuum chamber to solidify the quenched mixture in powder form within a mold. In an embodiment, the mold is made of graphite or tungsten carbide. In an embodiment, the mold is made of some other suitable mold material, which may be selected depending on the required pressure and solidification temperature. In an embodiment, the quenched mixture in powder form is solidified in a spark plasma sintering (SPS) machine. In an embodiment, solidification can be carried out in a conventional direct current hot press or an indirect heating hot press. In an embodiment, solidification is carried out at a pressure of 20 MPa to 100 MPa and a temperature near the melting point of component B. In an embodiment, during the sintering process, excess component B (if present) is ejected from the graphite mold, and particles with high density are obtained. A photograph of the solidified particles is shown. Figure 2 As shown.
[0054] In step 112, controlled consolidation is performed such that during the shaking step 104, liquefied component B spreads near the nanomaterial grains of component A and forms a honeycomb network morphology at the nanoscale upon solidification.
[0055] This invention also discloses heterostructure thermoelectric nanomaterials. In embodiments, the network heterostructure thermoelectric nanomaterial can be of formula Bi. x Sb 2-x D y M 3-y / Dδ Bi has two types of metal-semiconductor bulk heterostructures: p-type and n-type. x Sb 2-x D y M 3-y Component A is component B, and component D is component B. Elements D and M are selected from the group consisting of Te, Se, and S, and the values of x, y, and δ are in the range of 0 to 3. In the embodiment, the values of x, y, and δ are in the range of 0.1 to 1.
[0056] In this embodiment, component A may be selected from highly doped semiconductor thermoelectric nanomaterials. In this embodiment, component A is selected from materials with a carrier concentration range of 10-1. 19 / cm 3 Up to 10 21 / cm 3 p-type or n-type highly doped semiconductor nanomaterials.
[0057] In this embodiment, the nanostructure of the heterostructure thermoelectric nanomaterial forms a network heterostructure morphology at the nanoscale ranging from 1 nm to 10 nm. Component B has a honeycomb network structure with voids between the honeycomb network structures, and these voids are filled with component A.
[0058] In this embodiment, the grain size of component A in the heterostructure thermoelectric nanomaterial is in the range of 5 nm to 10 nm at the nanoscale. In this embodiment, the size of the component B layer in the heterostructure thermoelectric material is in the range of 1 nm to 5 nm at the nanoscale.
[0059] In the embodiments, tellurium, zinc, or bismuth is used as the B-component quantum well layer, and Sb is used. 2-x Bi x Using Te3 as the barrier layer of component A, p-type network heterostructure thermoelectric nanomaterials with improved efficiency can be obtained.
[0060] In the embodiments, tellurium, zinc, or bismuth is used as the B-component quantum well layer, and Bi2Te is used. 3-x Se x As a barrier layer for component A, it is possible to obtain n-type network heterostructure thermoelectric nanomaterials with improved efficiency.
[0061] In the embodiments, for p-type tellurium / Sb 2-x Bi x The Te3 heterostructure yielded a maximum Seebeck coefficient of 343.8 μV / K near room temperature. For p-type tellurium / Sb... 2-x Bi x The Te3 heterostructure exhibits a maximum conductivity of 6.5 × 10⁻⁶ near room temperature. 4 S / m. For p-type tellurium / Sb2-x Bi x The Te3 heterostructure achieves a maximum power factor of 7.6 mW / mK near room temperature. 2 For p-type tellurium / Sb 2-x Bi x The Te3 heterostructure exhibits a minimum thermal conductivity of 1.06 W / mK near room temperature. For p-type tellurium / Sb... 2-x Bi x The Te3 heterostructure exhibits a maximum thermoelectric figure of merit (ZT) of 2.1 near room temperature. For p-type tellurium / Sb... 2-x Bi x The Te3 heterostructure exhibits an average figure of merit (ZT) of 1.3 over the temperature range of room temperature to 250 °C. Furthermore, for p-type tellurium / Sb... 2-x Bi x The quantum confinement of the Te3 heterostructure was demonstrated at room temperature by the quantization plateau in the Hall resistance and the associated reduced longitudinal resistance peak as a function of the applied magnetic field.
[0062] In the embodiments, for n-type tellurium / Bi2Te 3-x Se x The heterostructure yielded a maximum Seebeck coefficient of 199.8 μV / K (negative) near room temperature. This is for n-type tellurium / Bi₂Te. 3-x Se x The heterostructure exhibits a maximum conductivity of 1.5 × 10⁻⁶ near room temperature. 5 S / m. For n-type tellurium / Bi2Te 3-x Se x The heterostructure achieves a maximum power factor of 6.1 mW / mK near room temperature. 2 For n-type tellurium / Bi2Te 3-x Se x The heterostructure achieves a minimum thermal conductivity of 0.71 W / mK near room temperature. For n-type tellurium / Bi₂Te 3-x Se x The heterostructure exhibits a maximum thermoelectric figure of merit (ZT) of 2.6 near room temperature. This is for n-type tellurium / Bi₂Te. 3-x Se x The heterostructure exhibits an average figure of merit (ZT) of 2.0 over a temperature range from room temperature to 250°C. Furthermore, for n-type tellurium / Bi₂Te... 3-x Se xThe quantum confinement of the heterostructure was demonstrated at room temperature by the quantization plateau in the Hall resistance and the associated reduced longitudinal resistance peak as a function of the applied magnetic field.
[0063] In the embodiments, the heterostructure of the thermoelectric material obtained by method 110 exhibits an improved Seebeck coefficient, increased electrical conductivity, decreased thermal conductivity, and thus an improved thermoelectric figure of merit. The sign of the Seebeck coefficient of the heterostructure of the thermoelectric material can be determined by the sign of the Seebeck coefficient of component A. Due to the quantum confinement effect, an increase in the Seebeck coefficient and / or electrical conductivity is obtained, thus resulting in a significant improvement in the power factor. Furthermore, n-type and p-type thermoelectric heterostructure materials can be realized by method 100.
[0064] In the embodiments, improved thermoelectric figure of merit for both p-type and n-type thermoelectric heterostructures is demonstrated in the same material system by simply changing the polarity of the semiconductor barrier layer. Method 100 provides a pair of materials for a practically effective thermoelectric device and discloses knowledge of carrier injection from the barrier layer to the quantum well layer for thermoelectric transport properties.
[0065] In this embodiment, quantum confinement in the heterostructure produced by method 100 is demonstrated by quantum well layers in the nanometer range using transmission electron microscopy. Furthermore, an improved power factor is shown in thermoelectric measurements and observations of the quantum Hall effect. The quantum confinement occurs in the metallic or semiconductor layer of component B. Additionally, for the quantum confinement obtained through the semiconductor thermoelectric nanomaterial barrier layer of component A, a band shift occurs. Therefore, a reduction in thermal conductivity is obtained due to the band shift value, which is higher than the typical phonon energy. Furthermore, in this method, carrier injection occurs from the barrier layer of component A to the quantum well layer of component B to obtain thermoelectric heterostructures of different polarities.
[0066] High-resolution transmission electron microscopy (HR-TEM) of thin sheets obtained from consolidated particles revealed unique morphological heterostructures at the nanoscale. Figure 3 HR-TEM images at the 100 nm scale show the honeycomb structure of component B, where the voids in this structure are filled by component A. Figure 4 In the HR-TEM image shown at the 50nm scale, structural details become more apparent.
[0067] exist Figure 5 and Figure 6The HR-TEM images at the 5 nm scale shown reveal atomic-level details of the heterostructure. These images depict identical atomic layers of component B and quintuplets of component A containing a different set of atoms repeating in the lattice. The layer size specifications of a few nm demonstrate the formation of the 2D heterostructure. As a result, a method for forming the network heterostructure of this disclosure is demonstrated.
[0068] Heterogeneous, consolidated particles were cut into appropriate shapes and sizes for thermoelectric measurements while maintaining directionality. Electrical conductivity and Seebeck coefficient were measured simultaneously. The system accuracy was checked using bismuth telluride according to NIST SRM 3451 standard. Thermal diffusivity was measured using a standard laser flash apparatus according to ASTM 1461 standard. Specific heat was measured using a differential scanning calorimeter with sapphire NIST SRM 720 standard. Room temperature density was determined using an Archimedes apparatus with 99.9% ethanol at standard density. Thermal conductivity was calculated by multiplying the measured thermal diffusivity, specific heat, and density values. Power factor and thermoelectric figure of merit were calculated based on the aforementioned measurement data.
[0069] The Seebeck coefficient measured for the heterostructured sample is significantly higher than the corresponding values for components A and B. Furthermore, the temperature dependence of the Seebeck coefficient does not correspond to that of components A and B. Therefore, entirely unique functional properties were obtained. This confirms the formation of a heterostructure between components A and B, and not merely the formation of a complex.
[0070] The conductivity values measured on the heterostructure sample are much higher than the corresponding values for component A, and close to the corresponding high values for component B. For the sample with an ideal semiconductor Seebeck coefficient, conductivity values within the half-metal range are shown.
[0071] The measured Seebeck coefficient and conductivity values indicate that the conventional relationship between the Seebeck coefficient and conductivity (often referred to as the Pisrenko relation) is disrupted. The Seebeck coefficient and conductivity are increased in the heterostructure. This improves the calculated power factor (Si). 2 The σ value is clear evidence of quantum confinement in heterostructures produced by the method of this invention.
[0072] The measured thermal diffusivity value may show a certain degree of increase, but this can be controlled by appropriately selecting the contents of components A and B. Specific heat is a bulk property, and the average effect of the corresponding values of components A and B can help control its value to some extent. The final calculated thermal conductivity value remains the corresponding value of component B and is much lower than the corresponding value of component A in bulk form.
[0073] The sign change of the Seebeck coefficient (p-type or n-type) of the heterostructures of components A and B is shown to vary with the type of charge carriers in component A. This demonstrates the charge injection mechanism for realizing both n-type and p-type thermoelectric heterostructures in the same material system.
[0074] The improvement in power factor, the control of thermal conductivity, and the alteration of charge carrier type by selecting component A have resulted in improved thermoelectric figure of merit values >2 for both n-type and p-type heterostructures. Thus, two efficient thermoelectric heterostructures, p-type and n-type, have been demonstrated in the same class of material systems with nearly identical temperature dependence of thermoelectric properties.
[0075] This invention utilizes a mesh-like heterostructure to demonstrate the knowledge of improving thermoelectric efficiency in heterostructures. This knowledge applies to all types of heterostructures, including superlattices, quantum wells, quantum wires, quantum dots, and combinations thereof.
[0076] This invention demonstrates improved thermoelectric efficiency in heterostructures by using component A as the semiconductor material and component B as the metal. This knowledge applies to semiconductors, metals, and insulators, as well as combinations thereof, of components A and B.
[0077] This invention demonstrates knowledge of improving thermoelectric efficiency in heterostructures using the size parameters and band shift values of components A and B. This knowledge applies to optimizing the dimensions of quantum wells and barriers, as well as optimizing the band shift values, through appropriate selection of components A and B and their combinations. Example
[0078] The following embodiments are given by way of illustration and should not be construed as limiting the scope of this disclosure. It should be understood that the foregoing general description and the following detailed description are merely exemplary and explanatory, and are intended to provide further explanation of the subject matter. This disclosure demonstrates a heterostructure Bi x Sb 2-x D y M 3-y / D δ Semiconductor Bi using Formula I x Sb 2-x D y M 3-y As component A, metal D is used as component B. In formula I, elements D and M can be selected from chalcogenides Te, Se, and S. Example 1: Te δ / Bi x Sb 2-x Te3 heterostructure
[0079] Using highly doped p-type semiconductor Bi x Sb 2-xTe3 nanomaterials are used as component A, and Te powder is used as component B. For component A, other options for component B include Bi, Zn, Sn, In, etc., which have melting points lower than Bi. x Sb 2-x Te3 is a melting point for metals and semiconductors.
[0080] Bi x Sb 2-x Nanomaterial powders of Te3 and Te were mixed together and filled into quartz ampoules. The values of both x and δ were in the range of 0.25 to 1. The ampoules were evacuated and purged with an inert gas, then sealed under vacuum conditions using a conventional LPG-oxygen combined flame. The sealed ampoule was placed in a shaking tube furnace and heated to approximately 400°C to melt Te without affecting Bi. x Sb 2-x Te3. Melt Te and Bi... x Sb 2-x The Te3 mixer was shaken for 1 to 5 hours and then rapidly cooled in air. The resulting sample was collected by breaking the ampoule and then ground into powder using conventional grinding methods.
[0081] The powder sample from the previous process is filled into a graphite mold. A graphite mold with an inner diameter between 10 mm and 40 mm is used, and this inner diameter can be any value depending on the sample size requirements. Tungsten carbide and other suitable mold materials can be used depending on the pressure and temperature requirements of the consolidation process. The powder sample inside the graphite is consolidated in a spark plasma sintering (SPS) machine. This consolidation is carried out for 2 to 15 minutes at a pressure range of 25 MPa to 100 MPa and a temperature near the melting point of Te, i.e., 400 °C. Other similar machines can also be used instead of SPS for consolidation, such as a direct current hot press (DCHP) or an indirect heating hot press. Excess Te is ejected from the graphite mold according to the δ value during this consolidation process.
[0082] Solid samples with thicknesses ranging from 2 mm to 15 mm are produced according to the requirements of the consolidation process. Any thickness can be used depending on requirements and resource availability. Solid samples are cut into different sizes and shapes for various thermoelectric and Hall measurements while maintaining directionality. Thin sections are also obtained from the solid samples for HR-TEM imaging.
[0083] HR-TEM imaging in Figures 3 to 6 The figures are shown in the diagram. These figures demonstrate that Te and Bi are in a honeycomb mesh morphology. x Sb 2- xThe network voids filled by Te3 nanomaterials form Te δ / Bi 0.5 Sb 1.5 Te3 heterostructure. Te can be... Figure 5 and Figure 6 Identify by the same type of atomic layer, and Bi x Sb 2-x Te3 can also be identified in these diagrams by quintuplets of various types of atoms. This provides a method for forming Te using the present invention. δ / Bi x Sb 2-x Te3 network heterostructure.
[0084] By using Te 8mm to 10mm (length) × 3mm to 4mm (width) × 1mm to 2mm (thickness) δ / Bi x Sb 2-x The Seebeck coefficient and conductivity of the Te3 heterostructure sample were simultaneously measured over a temperature range from room temperature to 250 °C. These measurements, with typical δ values, are plotted on [the graph]. Figure 7 and Figure 8 In. And only Bi x Sb 2-x Compared to Te3 (δ=0), the Seebeck coefficient in the heterostructure is increased. Compared to Bi only... x Sb 2-x Compared to Te3 (δ=0), the conductivity decreases at low temperatures. The increase in the Seebeck coefficient is more significant than the decrease in conductivity. This leads to an increase in the power factor, such as... Figure 9 The plotted result shows a peak power factor of 7.5 mW / mK. 2 Such a high power factor figure confirms that Te δ / Bi x Sb 2-x Quantum confinement effect in Te3 heterostructure.
[0085] Using a laser flash device, a Te film with a diameter of 12.7mm × 1mm to 2mm thickness is used. δ / Bi x Sb 2-x Thermal diffusivity of the Te3 heterostructure sample was measured in the temperature range from room temperature to 250 °C, and the results were plotted on [the graph]. Figure 10 The specific heat was measured using a differential scanning calorimeter over a temperature range from room temperature to 250°C. Density was measured at room temperature, and for the purpose of calculating thermal conductivity, it was assumed that the density was relatively constant over the temperature range of room temperature to 250°C. The thermal conductivity value, calculated by multiplying the measured thermal diffusivity, specific heat, and density values, was plotted on [the graph / plot]. Figure 11 middle.
[0086] Thermoelectric figure of merit was calculated at various temperatures using power factor and thermal conductivity values, and the results were plotted on [the graph]. Figure 12 This demonstrates Te δ / Bi x Sb 2-x The Te3 heterostructure achieves an improved thermoelectric figure of merit of 2.3. The highest average thermoelectric figure of merit obtained with this heterostructure is 1.3, with a peak value of 2.15. Te δ / Bi x Sb 2-x The thermoelectric parameters of the composition with the highest average thermoelectric figure of merit in the Te3 heterostructure are listed in Table 1. Table 1
[0087] Electrical transport properties in a magnetic field were investigated using a four-probe van der Pauw configuration with samples ranging in size from 8 mm to 10 mm × 8 mm to 10 mm × 0.7 mm to 0.9 mm. Measurements were performed over a temperature range from room temperature to 250 °C under a 9 kG magnetic field and a constant current of 5 mA. Resistivity and Hall voltage measurements were performed, and averaging was performed for geometry and current reversal to provide a practical estimate of the transport properties in these bulk samples. The oven containing the samples was evacuated and purged with helium to obtain stable measurement conditions. For p-type Te δ / Bi x Sb 2-x The calculated Hall mobility and carrier concentration values for the Te3 heterostructure are plotted on... Figure 13 middle.
[0088] p-type Te δ / Bi x Sb 2-x The Te3 heterostructure exhibits improved room-temperature mobility, which decreases with increasing temperature. Simultaneously, the carrier concentration increases with increasing temperature, and for bulk thermoelectric materials, the carrier concentration is highest at 10... 19 cm -3 Within the optimal range.
[0089] Using a Hall effect measurement system, Te film measuring 8mm to 10mm (length) × 8mm to 10mm (width) × 0.5mm to 0.9mm (thickness) was measured. δ / Bi x Sb 2-x Magnetic transport measurements were performed on a Te3 heterostructure sample. xy The Landau horizontal platform is displayed, along with the longitudinal resistance measurement (R). xxThe figure shows the initial valley value of the Landau plateau as a function of the applied magnetic field. Figure 14 plots R... xy and R xx The value is expressed as a function of the applied magnetic field at room temperature. This indicates that the quantized Hall plateau is associated with a reduced longitudinal resistance. For a single peak, this correlation is more pronounced in Figure 14(a), confirming the presence of a 2D transport contribution. xy Zhonglangdao Platform and R xx This correlation in the location of the mid-valley value shows that in Te δ / Bi x Sb 2-x The quantum Hall effect was observed in the Te3 heterostructure, thus establishing the quantum size effect in the Te produced in this invention. δ / Bi x Sb 2-x The role of Te3 in improving thermoelectric efficiency. Example 2: Te δ / Bi2Te 3-y Se y Heterogeneous structure
[0090] Using highly doped n-type semiconductor Bi2Te 3-y Se y Nanomaterials are used as component A, and Te powder is used as component B. For component A, other options for component B include Bi, Zn, Sn, In, etc., which have melting points lower than Bi₂Te. 3-y Se y Metals and semiconductors with high melting points.
[0091] Bi2Te 3-y Se y Nanomaterial powder and Te powder were mixed together and filled into quartz ampoules. The values of both y and δ were in the range of 0.25 to 1. The ampoules were evacuated and purged with an inert gas, then sealed under vacuum conditions using a conventional LPG-oxygen combined flame. The sealed ampoule was placed in a shaking tube furnace and heated to approximately 400°C to melt Te without affecting Bi₂Te. 3-y Se y . Melt Te and Bi2Te 3-y Se y The mixer was shaken for 1 to 5 hours and then rapidly cooled in air. The resulting sample was collected by breaking the ampoule and then ground into powder using conventional grinding methods.
[0092] The powder sample from the previous process is filled into a graphite mold. A graphite mold with an inner diameter between 10 mm and 40 mm is used, and this inner diameter can be any value depending on the sample size requirements. Tungsten carbide and other suitable mold materials can be used depending on the pressure and temperature requirements of the consolidation process. The powder sample inside the graphite is consolidated in a spark plasma sintering (SPS) machine. This consolidation is carried out for 2 to 15 minutes at a pressure range of 25 MPa to 100 MPa and a temperature near the melting point of Te, i.e., 400 °C. Other similar machines can also be used instead of SPS for consolidation, such as a direct current hot press (DCHP) or an indirect heating hot press. Excess Te is ejected from the graphite mold according to the δ value during this consolidation process.
[0093] Solid samples with a thickness ranging from 2 mm to 15 mm are produced according to the requirements of the consolidation process. Any thickness can be used depending on requirements and resource availability. Solid samples are cut into different sizes and shapes for various thermoelectric and Hall measurements while maintaining directionality.
[0094] By using Te 8mm to 10mm (length) × 3mm to 4mm (width) × 1mm to 2mm (thickness) δ / Bi2Te 3-y Se y The Seebeck coefficient and conductivity of the heterostructured sample were simultaneously measured over a temperature range from room temperature to 250 °C. These measurements, with typical δ values, are plotted on [the graph]. Figure 15 and Figure 16 In the middle. And only Bi2Te 3-y Se y Compared to (δ=0), the Seebeck coefficient in the heterostructure is increased. Compared to Bi2Te only... 3-y Se y Compared to (δ=0), conductivity also increases. The increase in Seebeck coefficient and conductivity leads to an increase in power factor, such as... Figure 17 The peak power factor obtained is 7.0 mW / mK. 2 Such a high power factor confirms Te δ / Bi2Te 3-y Se y Quantum confinement effect in heterostructures.
[0095] Using a laser flash device, a Te film with a diameter of 12.7mm × 1mm to 2mm thickness is used. δ / Bi2Te 3-y Se y The thermal diffusivity of the heterostructured sample was measured in the temperature range from room temperature to 250°C, and the results were plotted on [the graph]. Figure 18 The specific heat was measured using a differential scanning calorimeter over a temperature range from room temperature to 250°C. Density was measured at room temperature, and for the purpose of calculating thermal conductivity, it was assumed that the density was relatively constant over the temperature range of room temperature to 250°C. The thermal conductivity value, calculated by multiplying the measured thermal diffusivity, specific heat, and density values, was plotted on [the graph / plot]. Figure 19 middle.
[0096] Thermoelectric figure of merit was calculated at various temperatures using power factor and thermal conductivity values, and the results were plotted on [the graph]. Figure 20 This demonstrates Te δ / Bi2Te 3-y Se y The heterostructure improves the thermoelectric figure of merit by 2.6. The highest average thermoelectric figure of merit obtained by this heterostructure is 2.0. δ / Bi2Te 3-y Se y The thermoelectric parameters of the composition with the highest average thermoelectric figure of merit in the heterostructure are listed in Table 2. Table 2
[0097] Electrical transport properties in a magnetic field were investigated using a four-probe van der Pauw configuration with samples ranging in size from 8 mm to 10 mm × 8 mm to 10 mm × 0.7 mm to 0.9 mm. Measurements were performed over a temperature range from room temperature to 250 °C, under a 9 kG magnetic field and with a constant current of 5 mA. Resistivity and Hall voltage measurements were performed, and averaging was performed for geometry and current reversal to provide a practical estimate of the transport properties in these bulk samples. The oven containing the samples was evacuated and purged with helium to obtain stable measurement conditions. For n-type Te δ / Bi2Te 3-y Se y The calculated Hall mobility and carrier concentration values were plotted on Figure 21 middle.
[0098] In n-type Te δ / Bi2Te 3-y Se y In the case of heterostructure, a carrier concentration of 10 was observed. 20 cm -3This is a very high value within the range. Moreover, it does not exhibit much temperature dependence. The Hall mobility in this material is very low compared to the Hall mobilities reported for the constituent materials of the heterostructure. Furthermore, it does not exhibit much temperature dependence. At such high carrier concentrations, the reduced mobility in the n-type heterostructure may be associated with increased carrier-carrier scattering.
[0099] Using a Hall effect measurement system, Te film measuring 8mm to 10mm (length) × 8mm to 10mm (width) × 0.5mm to 0.9mm (thickness) was measured. δ / Bi2Te 3-y Se y Magnetic transport measurements were performed on a heterogeneous sample. Hall resistance (R) xy The Landau horizontal platform is displayed, along with the longitudinal resistance measurement (R). xx The figure shows the initial valley value of the Landau plateau as a function of the applied magnetic field. Figure 22 plots R... xy and R xx The value is expressed as a function of the applied magnetic field at room temperature. This indicates that the quantized Hall plateau is associated with a reduced longitudinal resistance. For a single peak, this correlation is more pronounced in Figure 22(a), confirming the presence of a 2D transport contribution. R xy Zhonglangdao Platform and R xx This correlation in the location of the mid-valley value shows that in Te δ / Bi x Sb 2-x The quantum Hall effect was observed in the Te3 heterostructure, thus establishing the quantum size effect in the Te produced in this invention. δ / Bi2Te 3-y Se y The role of heterostructures in improving thermoelectric efficiency.
Claims
1. A method (100) for synthesizing a network-like heterostructured nanomaterial, the method comprising: a. Mix the nanomaterial powder of component A with the powder of component B in a ratio selected from the range of 95:05 to 75:25 (102) to obtain the mixture thereon; b. The mixture obtained by heating under vacuum (104) to melt component B in the mixture, while shaking the mixture during heating; c. The heated mixture is quenched in air (106) to obtain a quenched mixture; d. Grind (108) the quenched mixture containing component A and component B into powder form; e. Filling (110) the quenched mixture in powder form into a pre-designed mold; and f. The quenched mixture in powder form (112) is solidified by sintering in a vacuum chamber to obtain the network heterostructured nanomaterial.
2. The method (100) of claim 1, further comprising selecting component A and component B from the group consisting of metals, semiconductors and insulators.
3. The method (100) of claim 1, further comprising selecting component A and component B such that the melting point of component A is greater than the melting point of component B.
4. The method (100) of claim 1, further comprising selecting component B from the group comprising tellurium, bismuth, and zinc, and selecting component A as Bi₂Te. 3-x Se x x is in the range of 0.1 to 1.
5. The method (100) of claim 1, further comprising selecting component B from the group comprising tellurium, bismuth, and zinc, and selecting component A as Sb. 2-x Bi x Te3, x is in the range of 0.1 to 1.
6. The method (100) of claim 1, further comprising selecting component B from the group consisting of Bi2Te3 and Sb2Te3, and selecting component A from the group consisting of Bi2Se3, Bi2S3, Sb2Se3 and Sb2S3.
7. A heterostructure thermoelectric nanomaterial having the formula Bi x Sb 2-x D y M 3-y / D δ Heterogeneous structure: Bi x Sb 2-x D y M 3-y Component A is component B and D is component B. Elements D and M are selected from the group including Te, Se, and S; the values of x, y, and δ are in the range of 0 to 3.
8. The heterostructure thermoelectric nanomaterial as described in claim 7, wherein the values of x, y, and δ are in the range of 0.1 to 1.
9. The heterostructure thermoelectric nanomaterial according to claim 7, wherein the nanostructure of the heterostructure thermoelectric nanomaterial forms a network heterostructure morphology at the nanoscale in the range of 1 nm to 10 nm, component B has a honeycomb network structure, there are gaps between the honeycomb network structures, and the gaps are filled with component A.
10. The heterostructure thermoelectric nanomaterial of claim 7, wherein the heterostructure thermoelectric nanomaterial comprises a layer of component B having a size in the range of 1 nm to 5 nm.
11. The heterostructure thermoelectric nanomaterial of claim 7, wherein the heterostructure thermoelectric nanomaterial comprises grains of component A having a size in the range of 5 nm to 10 nm.
12. The heterostructure thermoelectric nanomaterial as described in claim 7, wherein improving the thermoelectric efficiency of the network heterostructure includes: a. Quantum confinement in the metal or semiconductor layer of component B; b. Band shift of quantum confinement obtained through the barrier layer of semiconductor thermoelectric nanomaterials of component A; as well as c. Injecting charge carriers from the barrier layer of component A into the quantum well layer of component B to obtain thermoelectric heterostructures with different polarities.
13. The heterostructure thermoelectric nanomaterial according to claim 7, wherein the chemical potential of component B is lower than that of component A.
14. The heterostructure thermoelectric nanomaterial of claim 7, wherein component A comprises a carrier concentration in the range of 10. 19 / cm 3 Up to 10 21 / cm 3 It is selected from the group of p-type highly doped semiconductor nanomaterials and n-type highly doped semiconductor nanomaterials.
15. The heterostructure thermoelectric nanomaterial according to claim 7, wherein the sign of the Seebeck coefficient of the heterostructure is determined by the sign of the Seebeck coefficient of component A.
16. The heterostructure thermoelectric nanomaterial of claim 7, wherein the heterostructure thermoelectric nanomaterial has an increased Seebeck coefficient and / or conductivity, and an increased power factor due to quantum confinement in the heterostructure thermoelectric nanomaterial.
17. The heterostructure thermoelectric nanomaterial of claim 7, which has reduced thermal conductivity due to a band shift value higher than that of typical phonon energies.
18. The heterostructure thermoelectric nanomaterial of claim 7, wherein a p-type network heterostructure is obtained, wherein component B is selected from the group consisting of tellurium, zinc, and bismuth to form the quantum well layer of component B, and component A is selected as Sb. 2-x Bi x Te3 forms a barrier layer for component A.
19. The heterostructure thermoelectric nanomaterial as described in claim 18, wherein the heterostructure thermoelectric nanomaterial is p-type tellurium / Sb 2-x Bi x Te3 heterostructure.
20. The heterostructure thermoelectric nanomaterial of claim 7, wherein an n-type network heterostructure is obtained, wherein component B is selected from the group consisting of tellurium, zinc, and bismuth to form the quantum well layer of component B, and component A is selected as Bi₂Te. 3-x Se x To form a barrier layer for component A.
21. The heterostructure thermoelectric nanomaterial as described in claim 20, wherein the heterostructure thermoelectric nanomaterial is n-type tellurium / Bi₂Te 3-x Se x Heterogeneous structure.
22. The heterostructure thermoelectric nanomaterial as described in claim 19, wherein the p-type tellurium / Sb 2-x Bi x The maximum p-type Seebeck coefficient of the Te3 heterostructure near room temperature is 343.8 μV / K.
23. The heterostructure thermoelectric nanomaterial as described in claim 19, wherein the p-type tellurium / Sb 2-x Bi x The maximum electrical conductivity of the Te3 heterostructure near room temperature is 6.5 × 10⁻⁶. 4 S / m.
24. The heterostructure thermoelectric nanomaterial as described in claim 19, wherein the p-type tellurium / Sb 2-x Bi x The maximum power factor of the Te3 heterostructure near room temperature is 7.6 mW / mK. 2 .
25. The heterostructure thermoelectric nanomaterial as described in claim 19, wherein the p-type tellurium / Sb 2-x Bi x The minimum thermal conductivity of the Te3 heterostructure near room temperature is 1.06 W / mK.
26. The heterostructure thermoelectric nanomaterial as described in claim 19, wherein the p-type tellurium / Sb 2-x Bi x The maximum thermoelectric figure of merit ZT for the Te3 heterostructure near room temperature is 2.
1.
27. The heterostructure thermoelectric nanomaterial of claim 19, wherein the p-type tellurium / Sb 2-x Bi x The average thermoelectric figure of merit ZT for the Te3 heterostructure is 1.3 over the temperature range of room temperature to 250°C.
28. The heterostructure thermoelectric nanomaterial as described in claim 19, for the p-type tellurium / Sb 2-x Bi x The quantum confinement of the Te3 heterostructure was demonstrated at room temperature by the quantization plateau in the Hall resistance and the associated reduced longitudinal resistance peak as a function of the applied magnetic field.
29. The heterostructure thermoelectric nanomaterial as described in claim 21, tellurium / Bi₂Te 3-x Se x The maximum n-type Seebeck coefficient of the heterostructure near room temperature is (negative) 199.8 μV / K.
30. The heterostructure thermoelectric nanomaterial as described in claim 21, wherein the n-type tellurium / Bi₂Te 3-x Se x The maximum electrical conductivity of the heterostructure near room temperature is 1.5 × 10⁻⁶. 5 S / m.
31. The heterostructure thermoelectric nanomaterial as described in claim 21, wherein the n-type tellurium / Bi₂Te 3-x Se x The maximum power factor of the heterostructure near room temperature is 6.1 mW / mK. 2 .
32. The heterostructure thermoelectric nanomaterial as described in claim 21, wherein the n-type tellurium / Bi₂Te 3-x Se x The minimum thermal conductivity of the heterostructure near room temperature is 0.71 W / mK.
33. The heterostructure thermoelectric nanomaterial as described in claim 21, wherein the n-type tellurium / Bi₂Te 3-x Se x The maximum thermoelectric figure of merit (ZT) for the heterostructure near room temperature is 2.
6.
34. The heterostructure thermoelectric nanomaterial as described in claim 21, wherein the n-type tellurium / Bi₂Te 3-x Se x The average thermoelectric figure of merit ZT for the heterostructure is 2.0 over the temperature range of room temperature to 250°C.
35. The heterostructure thermoelectric nanomaterial as described in claim 21, for the n-type tellurium / Bi₂Te 3-x Se x The quantum confinement of the heterostructure was demonstrated at room temperature by the quantization plateau in the Hall resistance and the associated reduced longitudinal resistance peak as a function of the applied magnetic field.
Citation Information
Patent Citations
Thermoelectric device produced by quantum confinement in nanostructures
US20070084499A1
Quantum well thermoelectric module
US20110062420A1
Semiconductor nanowire thermoelectric materials and devices, and processes for producing same
US20140024202A1
Superlattice quantum well thermoelectric material
US5436467A
Superlattice quantum well material
US5550387A
Cited By
Nickel-chromium alloy material with negative Seebeck coefficient as well as preparation method and application of nickel-chromium alloy material
CN122303687A